2011
DOI: 10.1021/np100472d
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Sesqui- and Diterpenoids from the Argentine Liverwort Porella chilensis

Abstract: Four fusicoccane-type diterpenoids (1-4), including the new 1 and 2; four pinguisane-type sesquiterpenoids (5-8); and two aromadendrane-type sesquiterpenoids (9 and 10) were isolated from an Argentine collection of the endemic liverwort Porella chilensis. The biofilm formation of the human pathogen Pseudomonas aeruginosa was inhibited by compounds 3 (53 and 47%), 9 (45 and 41%), and 10 (48 and 37%) at 50 and 5 μg/mL, respectively. Compounds 3, 9, and 10 also produced a slight decrease in bacterial growth and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 40 publications
4
48
0
1
Order By: Relevance
“…But the presence of cinnamaldehyde in the M. koenigii EO has not been reported previously. The antibiofilm activities of spathulenol, cinnamaldehyde and linalool are well documented (Budzyńska et al 2011;Gilabert et al 2011;Khan & Ahmad 2012) as they inhibit the autoinducer molecules (AHLs). Therefore, the antibiofilm activity of the tested M. koenigii EO may be attributed to the presence of these compounds.…”
Section: Inhibition Of Biofilm Formation In P Aeruginosa Pao1mentioning
confidence: 99%
“…But the presence of cinnamaldehyde in the M. koenigii EO has not been reported previously. The antibiofilm activities of spathulenol, cinnamaldehyde and linalool are well documented (Budzyńska et al 2011;Gilabert et al 2011;Khan & Ahmad 2012) as they inhibit the autoinducer molecules (AHLs). Therefore, the antibiofilm activity of the tested M. koenigii EO may be attributed to the presence of these compounds.…”
Section: Inhibition Of Biofilm Formation In P Aeruginosa Pao1mentioning
confidence: 99%
“…2-en-1-ol, (+) spathulenol, isospathulenol, 1-Cyclohexanone, 2-methyl-2-(3-methyl-2-oxobutyl), hexadecanoic acid, methyl ester, 9,12-octadecadienoic acid (Z,Z)-(CAS), 17-octadecynoic acid, campesterol, Ergost-5-EN-3á-OL, calophyllolide, and many more compounds shown (Table 13) is known to have higher potential in combating bacterial, fungal, and viral pathogens. Some of the compounds were reported for its anti-cancer property [26][27][28]. A previous review on genus Wedelia concluded that the thorough screening of literature available on genus Wedelia depicted the fact that it is a popular remedy among the various ethnic groups, Ayurvedic, and traditional practitioners for the treatment of ailments.…”
Section: Resultsmentioning
confidence: 99%
“…The known compounds anadensin (4) [10], 2a-hydroxyfusicocca-3(4)-en-5-one (5), 3a-hydroxyfusicocca-2(6)-en-5-one (6) [11], and ptychantol A (7) [8] were identified by comparison of their NMR and MS data with reported data.…”
Section: Resultsmentioning
confidence: 99%